Vital Sign Monitoring in Car Seats Based on Electrocardiography, Ballistocardiography and Seismocardiography: A Review - Sidikova, Michaela; Martinek, Radek; Kawala-Sterniuk, Aleksandra; Ladrova, Martina; Jaros, Rene; Danys, Lukas; Simonik, Petr (Sensors (Basel, Switzerland), 2020)
This paper focuses on a thorough summary of vital function measuring methods in vehicles. The focus of this paper is to summarize and compare already existing methods integrated into car seats with the implementation of inter alia capacitive electrocardiogram (cECG), mechanical motion analysis Ballistocardiography (BCG) and Seismocardiography (SCG). In addition, a comprehensive overview of other methods of vital sign monitoring, such as camera-based systems or steering wheel sensors, is also presented in this article. Furthermore, this work contains a very thorough background study on advanced signal processing methods and their potential application for the purpose of vital sign monitoring in cars, which is prone to various disturbances and artifacts occurrence that have to be eliminated.
Keywords: Ballistocardiography; seismocardiography; ballistocardiography; Child Restraint Systems; electroencephalography; srdeční frekvence; dětské zádržné systémy; vital sign monitoring; Automobiles; automobily; Humans; Vital Signs; sensors; Signal Processing, Computer-Assisted; balistokardiografie; Electrocardiography; Heart Rate; electrocardiography; car seats; signal processing; elektrokardiografie; počítačové zpracování signálu; lidé; vitální znaky